3-phosphoinositide-dependent protein kinase-1 as an emerging target in the management of breast cancer - Fyffe, C.; Falasca, Marco (2013)
It should be noted that 3-phosphoinositide-dependent protein kinase-1 (PDK1) is a protein encoded by the PDPK1 gene, which plays a key role in the signaling pathways activated by several growth factors and hormones. PDK1 is a crucial kinase that functions downstream of phosphoinositide 3-kinase activation and activates members of the AGC family of protein kinases, such as protein kinase B (Akt), protein kinase C (PKC), p70 ribosomal protein S6 kinases, and serum glucocorticoid-dependent kinase, by phosphorylating serine/threonine residues in the activation loop. AGC kinases are known to play crucial roles in regulating physiological processes relevant to metabolism, growth, proliferation, and survival. Changes in the expression and activity of PDK1 and several AGC kinases have been linked to human diseases including cancer. Recent data have revealed that the alteration of PDK1 is a critical component of oncogenic phosphoinositide 3-kinase signaling in breast cancer, suggesting that inhibition of PDK1 can inhibit breast cancer progression. Indeed, PDK1 is highly expressed in a majority of human breast cancer cell lines and both PDK1 protein and messenger ribonucleic acid are overexpressed in a majority of human breast cancers. Furthermore, overexpression of PDK1 is sufficient to transform mammary epithelial cells. PDK1 plays an essential role in regulating cell migration, especially in the context of phosphatase and tensin homologue deficiency. More importantly, downregulation of PDK1 levels inhibits migration and experimental metastasis of human breast cancer cells. Thus, targeting PDK1 may be a valuable anticancer strategy that may improve the efficacy of chemotherapeutic strategies in breast cancer patients. In this review, we summarize the evidence that has been reported to support the idea that PDK1 may be a key target in breast cancer management. © 2013 Fyffe and Falasca.